Bridging Macro–Microscopic Parameters: Correspondence and Calibration Approaches - Wei Li; Fengling Ji; Xiangsheng Chen (Applied Sciences)
Clarifying the correlation between macro–microscopic granular parameters and establishing effective parameter calibration methods for determining granular microparameters is of great importance for numerical simulations of granular flows. Currently, there is a gap in the systematic study of small particles, using sandy soil as an example, and the development of rational and effective calibration methods. Through inter-particle friction experiments, particle–wall friction experiments, uniaxial compression experiments and numerical simulations, we studied the relationship between macroscopic and microscopic parameters. Based on these studies, appropriate empirical formulas were proposed, and based on the correlation of macroscopic and microscopic parameters, a method for calibrating microscopic parameters was presented. This approach uses empirical formulas for macroscopic and microscopic parameters in combination with the constraints imposed by the granular stiffness coefficient to calibrate granular parameters. This study provides a systematic process framework for the calibration of microscopic parameters of small particles, standardizing the parameter calibration process and improving both efficiency and quality.